(untitled) (Student Conference Proceedings, 2025)
This study focuses on the permeabilization behavior of lipid bilayer membranes composed of natural and synthetically produced phosphatidylcholines, in the presence of mycobacterial glycolipid trehalose-6,6’-dimycolate (TDM). The experiments were conducted in the presence of the alpha-helical antimicrobial peptide (AMP) LL32, known for its ability to interact with and disrupt lipid bilayers. Reconstituted lipid bilayers were used to model the biological membrane and to investigate the influence of TDM on the interactions between LL32 and the lipid bilayer. By evaluating membrane integrity, the results provide insights into the effects of TDM on membrane stability and peptide-lipid interactions. This research helps to understand the modulation of membrane integrity by lipids and their role in peptide-mediated permeabilization, with implications for antimicrobial mechanisms and potential future therapeutic applications.